Use of the Oxford face matching test reveals an effect of ageing on face perception but not face memory. (December 2021) - Stantić, Mirta; Hearne, Bethan; Catmur, Caroline; Bird, Geoffrey
Abstract: Effects of ageing on both face perception and face memory have previously been reported. Previous studies, however, have not controlled for the effects of face perception when assessing face memory, meaning that apparent effects of ageing on face memory may actually be due to effects of ageing on face perception. Here, both face perception and face memory were assessed in a sample of adults ranging in age from 18 to 93, and the effect of age on face memory was assessed after controlling for face perception. Face perception was assessed using both a standard test and the Oxford face matching test (OFMT), deliberately designed to avoid the bias towards younger, neurotypical samples that may be present in other tests. An effect of ageing on face perception was found using both tests, with the unbiased OFMT being more sensitive to the effect of age. Importantly, when controlling for face perception using the OFMT, no effect of age on face memory was found. Indicative scores on the OFMT from a sample of 989 participants are provided, broken down by age and gender.